Oscar Wilde (Journal of Parents and Teachers, 2014)
The article deals with the history and life of the writer Oscar Wilde. The article is accompanied by activities and didactic proposals for Secondary and Baccalaureate about key concepts related to the world of literature and ethics.
Keywords: Oscar Wilde, Literature, Biography, Secondary Education, Baccalaureate